ANALISIS LARANGAN KEANGGOTAAN PARTAI POLITIK BAGI PENGURUS RUKUN TETANGGA DAN RUKUN WARGA DITINJAU DARI PERSPEKTIF HAK POLITIK SEBAGAI PRINSIP HAK ASASI MANUSIA - Sianipar, Erick Clark; Isharyanto, Isharyanto (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2020)
This study analyzes and examines the prohibition of political party membership for RT and RW management which is then reviewed in the perspective of political rights. This research is a prescriptive and applied normative legal research to analyze the ban on political party membership for RT and RW officials and to provide an ideal arrangement recommendation for the prohibition phrase in order to create neutrality for the institution without eliminating public participation in democracy. This study uses primary data in the form of literature study results and secondary data consisting of primary legal materials and secondary legal materials.This research shows that regulating the prohibition for RT and RW management to be affiliated with political parties is an effort to maintain the neutrality and independence of the institution in carrying out its functions specifically in community empowerment. Political rights in principle are included in the rights that can be deducted in certain cases so that the regulation of the ban does not completely harm the political rights of citizens.